Preparation and characterization of PVA/PMMA blend film as electrolyte in lithium ion battery / Siti Fatimah Mohammad Yaacob - Mohammad Yaacob, Siti Fatimah (2008)
In this study PVA/PMMA blend was prepared by solvent casting. There was no free standing film can be obtained from all blends composition. From the optical micrograph, it was noted that the swelling morphology of PVA due to the entrapment of moisture has been reduced when PMMA was added. The infra red (FTIR) analysis revealed that there was an interaction between PMMA and PVA via hydrogen bonding. Due to the presence of hydrogen bonding, the glass transition temperature (Tg) of the blend system increases as the amount of PMMA was increased. Overall, the PVA/PMMA blends were less stable than in their individual film